2008
DOI: 10.1093/rheumatology/ken376
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the MHC Class III region demonstrates association of AIF1 and rheumatoid arthritis

Abstract: The results of the genotyping and expression studies presented here suggest a role for AIF1 in both the aetiology and pathogenesis of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…However, it is intriguing that rs3132453 and additional PRRC2A SNPs are associated with other immune-related diseases such as rheumatoid arthritis 23 and atopic asthma. 24 Despite several disease associations with SNPs in or near PRRC2A, the gene's biologic function remains largely unknown. More is known of the involvement of a nearby apoptotic regulator gene, BAG6 (BAT3), in immune function and tumorigenesis.…”
Section: Rows 8 and 9)mentioning
confidence: 99%
“…However, it is intriguing that rs3132453 and additional PRRC2A SNPs are associated with other immune-related diseases such as rheumatoid arthritis 23 and atopic asthma. 24 Despite several disease associations with SNPs in or near PRRC2A, the gene's biologic function remains largely unknown. More is known of the involvement of a nearby apoptotic regulator gene, BAG6 (BAT3), in immune function and tumorigenesis.…”
Section: Rows 8 and 9)mentioning
confidence: 99%
“…A variety of diseases, ranging from cancer to autoimmune disorders and diabetes, are linked to Bag6 (33)(34)(35)(36)(37). Despite this demonstrated importance, structural characterization of the Bag6 complex is lacking.…”
mentioning
confidence: 99%
“…In another study, we have shown that the AIF1 rs2259571 CC genotype is associated with active form of RA. 7 The important role of AIF1 gene polymorphisms in RA pathogenesis was indicated in a study by Harney et al 12 which examined the AIF1 gene rs2269475 and rs2259571 polymorphisms in RA patients. These authors have shown a significant association between RA and AIF1 haplotypes independent of human leukocyte antigen-DRB1 (HLA-DRB1).…”
Section: Discussionmentioning
confidence: 99%